Vitamin E, Atherosclerosis and Thrombosis - Violi, Francesco; Micheletta, Fausta; Iuliano, Luigi (Thrombosis and Haemostasis, 2001)
Vitamin E, a major lipid-soluble, chain-breaking antioxidant includes several tocopherols having the biological activity of RRR-alpha-tocopherol. Vitamin E circulates in the blood as free tocopherol bound to beta-lipoproteins and is present in cell membrane where it exerts a potent defence against lipid peroxidation (1). Blood concentration of vitamin E in humans ranges from 25 to 30 μM, depending on daily intake and body’s ability to absorb fat (1). In the last decade the scientific interest on biological activity of vitamin E increased because of a growing body of evidence linking this vitamin with atherosclerosis and its complications (2). Thus, the oxidative hypothesis of atherosclerosis suggests that LDL accumulates within vessel wall, in particular in the macrophages, as a consequence of its oxidative modification mediated by resident cells (3, 4). A reduced defence against LDL oxidation could favour this process and accelerate atherosclerotic progression. Accordingly, patients with coronary heart disease have lower plasma concentration of vitamin E than controls (2) and prospective studies demonstrated that a daily assumption of vitamin E reduces cardiovascular events (5). According to the oxidative hypothesis of atherosclerosis, this effect has been attributed to the inhibition of LDL oxidation. Alternative mechanism potentially implicated in the antiatherosclerotic activity of vitamin E includes its interference with the activity of platelet and monocyte, in which the intracellular redox status plays an important functional role (6, 7). As platelets and monocytes are both involved in the pathophysiologic process leading to atherosclerotic lesion, the interference of vitamin E with the biological function of these cells may represent another important tool to explore the anti-atherosclerotic activity of vitamin E. This review will focus on the open issues related to the use of vitamin E in clinical studies and the potential usefulness in investigating platelet function and clotting activation in patients treated with vitamin E.